Reflecting non-verbal cues in the context of crisis: the fist and the open palm in Zimbabwe's political crisis - Saidi, Umali (David Publishing, 2017)
The Zimbabwean political landscape has given rise to many interpretations. Violence, intimidation, and propaganda have been part of this crisis leading to serious economic and social problems for the ordinary person. The two main political parties in the country have used party signs and symbols to assert their ideology. This paper employs the semiotic theory to explore how the ZANU PF (Zimbabwe African National Union Patriotic Front) party sign or symbol the clenched fist as well as the MDC T (Movement for Democratic Change—Tsvangirai)’s open palm, the same hand but communicating two conflicting political ideologies as non-verbal cues reveal party ideology and identity and in some cases become the cause of either conflict or harm on party followers. Semiotics offers us a platform to theorize as well as gain semantic realizations of signs and symbols as used to communicate in various contexts. Because non-verbal cues of various nature are in fact signs and symbols largely decoded by the eye, semiotics allows us to give attention to even non-verbal cues which they themselves have received less attention in communication studies yet they are found to be 60% responsible for meanings realized in any communication situation